Waste polyethylene terephthalate plastic derived Zn-MOF for high performance supercapacitor application - Abdullah M. Al-Enizi; Ayman Nafady; Nouf B. Alanazi; Meera Moydeen Abdulhameed; Shoyebmohamad F. Shaikh (Journal of King Saud University: Science, 2024)
A simple chemical approach was used to prepare Zn-MOF or MOF-5 derived from polyethylene terephthalate bottles for supercapacitor applications. The morphology, and structure of PET-derived MOFs were characterized using various techniques, including scanning electron microscopy, transmission electron microscopy, X-ray diffraction, thermogravimetric analysis, fourier transform infrared spectroscopy, and BET surface area and nitrogen adsorption/desorption analysis. The BET surface area of MOF-5 was determined to be 88 m2g−1 and N2 adsorption–desorption analysis, showed the type-IV isotherms and suggest the existence of capillary condensation within the meso- and micropore structures. An excellent specific capacitance ranging from 341 to 191 F g−1 recorded form the scan rate of 2–200 mV s−1 by CV for Zn-MOF. Moreover, the highest specific capacitance 353 F g−1 calculated at 0.5 A/g current density. The highest value of specific capacitance Cs 353 F g−1 was found for lowest current density of 0.5 A/g. An excellent cyclic stability was obtained after running 2000 cyclic runs at a scan rate of 50 mV s−1. The small semicircle of EIS plot exhibits superior electrochemical performance of the Zn-MOF. The waste PET plastic derived Zn-MOF showed an excellent supercapacitor performance which can be utilized in energy storage applications. This approach not only facilitates environmental remediation but also offers a valuable organic linker for energy material synthesis.